2013
DOI: 10.1371/journal.pone.0073679
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a Panel of Biomarkers with the Presence and Severity of Carcinoid Heart Disease: A Cross-Sectional Study

Abstract: PurposeMetastatic neuroendocrine tumors secrete serotonin and other vasoactive substances that are responsible for carcinoid syndrome and carcinoid heart disease. We sought to evaluate the discriminatory utility of diagnostic biomarkers in determining the presence and severity of carcinoid heart disease in patients with metastatic neuroendocrine tumors.Patients and methodsA cross-sectional study of patients with neuroendocrine tumors with documented liver metastases and/or carcinoid syndrome between April 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 30 publications
13
69
0
Order By: Relevance
“…NKA levels are considered to have utility in evaluating carcinoid heart disease and treatment responses (Dobson et al 2013). It has been suggested that levels may be an independent indicator of NET prognosis; O 50 pmol/l associated with decreased 3 year survival rates (Turner et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…NKA levels are considered to have utility in evaluating carcinoid heart disease and treatment responses (Dobson et al 2013). It has been suggested that levels may be an independent indicator of NET prognosis; O 50 pmol/l associated with decreased 3 year survival rates (Turner et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the diagnostics and assessment of the severity of carcinoid heart disease, the determination of 5-HIAA and NT-proBNP (N-terminal-pro-B-type natriuretic peptide) may be useful [3,34,38].…”
Section: Laboratory Diagnosticsmentioning
confidence: 99%
“…If the disease progresses, follow-up imaging and biochemical tests need to be conducted more frequently -every three months [38,110].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Heart failure resulting from expansion of the disease to the cardiac cavities is associated with shortened life expectancy in patients, and it requires proper cardiological and/or cardiosurgical treatment [21,31]. Other comments on treatment with SSA: -It is recommended to discontinue SSA before the planned receptor examinations SPECT or PET-CT: at least four weeks in the case of long-acting preparations, and 24-48 hours for short-acting ones.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%